Development of the Principle of Legality in Indonesian Criminal Law - Sitorus, Tonggo; Harahap, Muhammad Rafandi; Sembiring, Ferdinand; Hasibuan, Syaiful Asmi (PT. Riset Press International, 2024)
Legality is the oldest principle of criminal law and is found in almost all national criminal laws worldwide. The existence of this principle is to protect citizens from the arbitrariness of the authorities. The principle of legality in criminal law has a central role in ensuring legal certainty for society because this principle requires the existence of written regulations regarding a criminal act to carry out a punishment. The aim is to understand the principles of legality according to criminal law in Indonesia. The research used normative juridical methods with data collection methods through a literature study. The principle of legality in Indonesian criminal law is a fundamental principle. The principle of legality in criminal law is essential to determine whether or not a criminal law regulation can treat a criminal act that has occurred. Applying the principle of good legality in national criminal law is not rigid, mainly to tackle crimes against human rights.